Analysis of the interactions between difluoroacetylene and one or two hydrogen fluoride molecules based on calculated spin-spin coupling constants - Provasi, Patricio Federico (2012)
A theoretical study of FCCF:(HF). n complexes, with n= 1 and 2, has been carried out by means of ab initio computational methods. Two types of complexes are formed: those with FH. ...π interactions and those with FH. ...FC hydrogen bonds. The indirect spin-spin coupling constants have been calculated at the CCSD/aug-cc-pVTZ-. J computational level. Special attention has been paid to the dependence of the different intramolecular coupling constants in FCCF on the distance between the coupled nuclei and the presence or absence of the hydrogen fluoride molecule. The sensitivity shown by these coupling constants to the presence of hydrogen fluoride is quite notorious.